Methods in the history of economic thought - Cardoso, José Luís (2017)
The practitioners of the history of economic thought engage frequently in discussion on issues relating to its subject-matter and method. It is because those who study this discipline like to feel firm ground beneath their feet that retrospective overviews and prospective considerations are presented cyclically, expressing concerns and hopes about the present and future situation of this field of knowledge. The places normally chosen for this purpose are the conferences promoted by the main international academic associations and scientific societies that each year bring together the members of this community. The testimonies of Donald Winch (2000), Heinz D. Kurz (2006) and E. Roy Weintraub (2007) are a clear illustration of this type of exhortation, while at the same time revealing quite different commitments and distinct ways of conceiving the existence of the history of economic thought or the history of economics. This contribution will be precisely devoted to clarify the methodological distinctions as well as the plurality and complementarity of methods practiced by historians of economic thought. Despite their differences of content and style, these approaches come together in their unequivocal defence of the rights acquired by a discipline that has already found a direction and sets great store in discussing its identity. Therefore, the next section will briefly refer to the key ontological question of the actual object itself that affords both autonomy and identity to this academic endeavour of revisiting the past of economics.